Tsunami Evacuation Route Optimization Based on Megathrust Scenario Modeling in Pangandaran, West Java, Indonesia - Wijayanto, Mirda Prisma; Achmad, Arifin; Muflihatun; Mahfud, Chiquita Laila; Apriyanti, Syafrida Dwi; Zakia, Zulfa Siti (UIR PRESS, 2025)
The southern coastal area of West Java, particularly Pangandaran, faces a high risk of tsunami disasters triggered by megathrust earthquakes. However, current evacuation strategies in the region often lack integration between seismic hazard analysis, tsunami wave propagation modeling, and evacuation route optimization. To address this gap, this study aims to develop an integrated framework that combines seismicity assessment, tsunami simulation, and optimal evacuation planning for the Pangandaran coastal region. Seismic records from 2000 to 2024 indicate a total of 3090 earthquake events, predominantly offshore, with magnitudes ranging from low to moderate. The estimated b-value (1.19 ± 0.04) and a-value (8.057) reflect significant tectonic stress within the subduction zone between the Indo-Australian and Eurasian plates. Spatial analysis highlights offshore zones as areas of elevated seismic risk with the potential for large-magnitude events. Tsunami modeling was performed using the COMCOT model under a scenario of an 8.7 Mw megathrust earthquake. The simulation revealed maximum wave heights of up to 18.59 meters, reaching the coast within 40–45 minutes. Natural features such as coastal conservation zones were observed to reduce wave intensity, underscoring their role in hazard mitigation. Evacuation route modeling was carried out using Dijkstra’s algorithm, with two designated starting points located in the eastern and western sectors of Pangandaran Beach. The optimal routes identified to a designated Temporary Evacuation Site (TES) produced travel distances of 1.093 km and 0.533 km, requiring 26.23 and 12.79 minutes respectively, both within the available time window before tsunami impact. The findings offer actionable input for local disaster preparedness and evacuation planning. Furthermore, this study demonstrates the practical application of graph theory in disaster mitigation and provides a scalable framework for tsunami-prone regions worldwide.